Mining and Motivation: Impacts on Al-Ishlah Bobos Islamic Cooperative Development - Komarudin, Udin (Journal of Economicate Studies, 2021)
This study examines the socio-economic impact of C Gunung Kuda mining on the Al-Ishlah Bobos Islamic Boarding School Cooperative in Cirebon Regency, Indonesia. Drawing upon Maslow’s motivation theory, Islamic economic principles, and cooperative institutional models, it explores how extractive industrial activities influence member motivation and economic behavior. The research employs qualitative document analysis to uncover thematic patterns of behavioral change, institutional adaptation, and ethical tension. Findings reveal a shift from intrinsic, faith-driven motivation to extrinsic, profit-oriented engagement among cooperative members. Economic disruptions include declining collective investment and weakened operational stability. The cooperative faces a conflict between maintaining Islamic ethical standards and adapting to external industrial pressures. This study contributes to theoretical discourse by integrating religious and motivational frameworks and offers practical guidance for resilience in sharia-based cooperatives facing industrial encroachment. The implications highlight the need for policy alignment and ethical adaptation strategies to preserve cooperative sustainability and spiritual integrity.